Antioxidant and Alpha-Glucosidase Inhibitory Activity of Durio zibethinus L. Clone 175 (Durian Udang Merah) Shell and UHPLC-ORBITRAP-MS Profiling of the Extract - Wan Zain, Wan Muhd Hatim; Mediani, Ahmed; Zolkeflee, Nur Khaleeda Zulaikha; Wong, Pei Lou; Abas, Faridah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Durio zibethinus or ‘durian’ is a well-known seasonal fruit of Southeast Asia and has been called the ‘King of Fruit’. The popularity of durian has led to large production of this crop in Malaysia, consequently creating a huge agricultural waste including the shell. Despite illness remedies from various parts of durian, the information on phytochemical constituents and bioactivities of durian shells remained scarce. Therefore, this study aimed to evaluate the total phenolic content (TPC), antioxidant, and α-glucosidase inhibitory activities of D. zibethinus shell extracted with different ethanol percentage (0%, 50%, and 100%). Results showed that the 100% ethanolic extract exhibited the highest 2,2-dipheny-1-picrylhydrazyl (DPPH) free radical scavenging activity with an IC50 value of 96.91 ± 1.09 µg/ mL. Furthermore, the 50% ethanol extract exhibited the highest TPC with 130.57 ± 1.92 mg GAE/g crude extract, and nitric oxide (NO) scavenging activity with an IC50 value of 435.30 ± 3.41 µg/mL. Both 50% and 100% ethanolic extracts of D. zibethinus shell exhibited great potential in α-glucosidase inhibitory activity with IC50 values of 1.99 ± 0.90 and 4.53 ± 0.21 µg/mL, respectively. Thus, the bioactive compounds in 100% ethanolic extract of D. zibethinus were profiled by ultra-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) analysis. A total of 20 compounds were tentatively identified, including flavonoids, alkaloids, benzofurans, terpenoids, pentose phosphate, organosulfur compounds, organooxygen compounds, polyketides, carotene, carboxylic acid, coumarin, and stigmasterol. In conclusion, durian shell exhibits potential for future applications driven by its inherent pharmacological benefits, consequently contributing to waste reduction.